When all rankings do is rankle - Abd Razak, Dzulkifli (2009)
FORMER United Nations secretarygeneral Kofi Annan remarked recently in Kenya that 95 per cent of new science is created in countries where onefifth of the world's population lives. This being the case what is the real meaning of world ranking of universities? Perhaps that is why so many global goals and agendas do not go beyond lip service. These range from global warming and climate change (the Kyoto Protocol expires in 2012) to the UN Millennium Development Goals (MDGs) and the UNESCOled Education for All! initiative (both of which will end in 2015).